Cook Inlet beluga whale calling varies by group characteristics, behavior, and tidal state - Arial M. Brewer; Amy M. Van Cise; Christopher Garner; Andrea Gilstad; Manuel Castellote; Sarah J. Converse; Kimberly T. Goetz; Andrew M. Berdahl (Behavioral Ecology and Sociobiology, 2026)
Communication allows social species to exchange information among group members. In aquatic environments, acoustic signals are among the most effective forms of communication and are important for many species, including cetaceans. Beluga whales ( Delphinapterus leucas ) are highly social and vocal, yet little is known about the functionality of their social calls. To examine context-dependent vocal behavior in belugas, we collected passive acoustic data and fine-scale behavioral observations for the endangered Cook Inlet beluga population. The resulting dataset includes 1,720 annotated vocalizations collected over 21 behaviorally encoded encounters. We fit generalized linear mixed models to these data to investigate the effect of behavioral state, group size, calf presence, and tidal state on (1) calling rate (number of calls/minute) and (2) call category (whistles, pulsed calls, combined calls). Belugas were more likely to call when traveling and had higher calling rates during flood tides. Group-level calling rate increased sublinearly with group size, suggesting that individuals called less in larger groups, possibly reflecting increased listening, vocal coordination, or a strategy to avoid acoustic masking. Group calling rate increased before transitions between traveling and milling, suggesting a possible link between communication and behavioral transitions. Whistles were more prevalent when traveling, while pulsed calls were more prevalent when milling. Combined calls occurred only when calves were present, indicating the importance of these calls in communication with calves. Identifying these communication patterns and the contexts in which they occur can enhance our understanding of beluga whale ecology and aid in conservation efforts via passive acoustic monitoring.

Lead and other Trace Elements in Spices in the Las Vegas Market: Human Health Risk Assessment - Douglas B. Sims; Desta Woldetsadik; Joshua R. Monk; Mark C. Garner; Christopher Adcock; Emmanuel Herrera Huerta; Timothy Nelson; Amanda C. Hudson (Biological Trace Element Research, 2026)

Occurrence and Ecotoxicological Risks of Pharmaceuticals and Illicit Drugs in Effluent and Unsheltered Homelessness-Impacted River Systems - Douglas B. Sims; Joshua R. Monk; Desta Woldetsadik; Andressa C. Buch; Amanda C. Hudson; Mark C. Garner; Joseph Piacentini; Christopher Cohu; Chris S. Duvall; Jasmine Krause; Meaghan E. Hickey; Matthew Glazewski; et al. (Archives of Environmental Contamination and Toxicology, 2026)

Mineral profile of infant formula in the Las Vegas market: Compliance with label and regulations, contribution to dietary reference intakes and method comparison - Desta Woldetsadik; Douglas B. Sims; Emmanuel Herrera Huerta; Timothy Nelson; Abigael Walker; Joshua Monk; Mark C. Garner; Christopher Adcock; Amanda C. Hudson; David E.B. Fleming (Food and Chemical Toxicology, 2025)

Methylocystis suflitae as a promising industrial workhorse for methane-based polyhydroxyalkanoate production - Eleni N. Moutsoglou; Dipayan Samanta; Tanvi Govil; Lee R. Krumholz; Christopher T. Garner; Rajesh K. Sani (Systems Microbiology and Biomanufacturing, 2025)

Using passive acoustics to identify a quiet winter foraging refuge for an endangered beluga whale population in Alaska - Manuel Castellote; Verena A. Gill; Christopher D. Garner; Andrea J Gilstad; Benjamin X. Hou; Arial M. Brewer; Jessica M. Knoth (Frontiers in Marine Science, 2024)
Cook Inlet beluga (CIB), Delphinapterus leucas , have not recovered from subsistence overharvest despite conservation efforts initiated in 2000. Reasons for this lack of recovery are still unclear with anthropogenic noise identified as a high threat in this population’s recovery plan. Baseline information on CIB habitat use and soundscape characterization is crucial in evaluating impacts from anthropogenic activities. Using passive acoustic monitoring, we documented the seasonality and foraging occurrence of CIB, together with killer whale ( Orcinus orca ), harbor porpoise ( Phocoena phocoena ) and humpback whale ( Megaptera novaeangliae ), for one year in Chinitna and Tuxedni bays and rivers, two historically important but recently overlooked areas of their critical habitat in western lower Cook Inlet, Alaska. This area’s ecological interest converges with planned mining, marine renewable energy, offshore oil and gas production, and commercial shipping. Results revealed higher presence of harbor porpoise, killer whale, and humpback whale in Chinitna compared to Tuxedni but much lower CIB presence. CIB were not detected in Chinitna Bay but were in the river on 21 days September-February and one day in June. However, CIB were never detected feeding in Chinitna River. CIB acoustic crypsis and preferential use of very shallow habitat in Chinitna revealed a perceived predation risk from killer whales. In contrast, CIB were recorded foraging in both Tuxedni Bay and River and were detected September-April on 127 days making it an important winter foraging ground. Low levels of anthropogenic noise disturbance were quantified in both bays making them some of the most undisturbed sections of their critical habitat, but at the same time highly sensitive to further noise disturbance. Commercial shipping was the main noise source likely causing acoustic disturbance to CIB due to communication masking despite current low levels of temporal overlap with beluga presence. We recommend that applicable regulators consider restricting high sound producing anthropogenic activities in and adjacent to Tuxedni Bay from September 1st to May 15th when CIB are actively using this area. Managing future anthropogenic activities to minimize habitat degradation and acoustic disturbance in this winter foraging refuge will be a key component to support the recovery of this endangered population.

Patterns of mortality in endangered Cook Inlet beluga whales: Insights from pairing a long‐term photo‐identification study with stranding records - Tamara L. McGuire; Kim E. W. Shelden; Gina K. Himes Boor; Amber D. Stephens; John R. McClung; Christopher Garner; Caroline E. C. Goertz; Kathleen A. Burek‐Huntington; Greg O'Corry‐Crowe; Bruce Wright (Marine Mammal Science, 2021)
Mortality is a demographic metric crucial for understanding the dynamics of endangered populations such as Cook Inlet beluga whales (CIBWs, Delphinapterus leucas ), but patterns of mortality are currently not well understood for CIBWs, making decisions about recovery actions challenging. We combined long‐term photo‐ID data from approximately 420 individual belugas identified during the period 2005–2017 with stranding data from 95 dead belugas to identify patterns of mortality with respect to age, sex, geographic range, cause of death, and to estimate minimum mortality rates. Reported mortality was greatest for adults of reproductive age, followed by calves, with fewer subadults and no adults older than 49 years in the stranding data set despite lifespans of 70+ years reported in other beluga populations. Dead females and males were evenly represented. Live stranding was the predominant assigned cause of death but represented only ~33% of deaths of known cause. Causal factors for the majority of deaths and live strandings are unknown. Annual mortality estimated from reported carcasses relative to total population size averaged 2.2%. Our analysis advances our current understanding of mortality patterns in CIBWs but linking a greater proportion of carcasses to photo‐ID individuals would further improve our understanding; we conclude with recommendations for achieving this.

Reproductive natural history of endangered Cook Inlet Beluga whales: insights from a long-term photo-identification study - Tamara L. McGuire; Amber D. Stephens; John R. McClung; Christopher D. Garner; Kim E. W. Shelden; Gina K. Himes Boor; Bruce Wright (Polar Biology, 2020)

Neurite outgrowth inhibitory levels of organophosphates induce tissue transglutaminase activity in differentiating N2a cells: evidence for covalent adduct formation - Ibtesam S. Almami; Maha A. Aldubayan; Shatha G. Felemban; Najiah Alyamani; Richard Howden; Alexander J. Robinson; Tom D. Z. Pearson; David Boocock; Alanood S. Algarni; A. Christopher Garner; Martin Griffin; Philip L. R. Bonner; et al. (Archives of Toxicology, 2020)
Organophosphate compounds (OPs) induce both acute and delayed neurotoxic effects, the latter of which is believed to involve their interaction with proteins other than acetylcholinesterase. However, few OP-binding proteins have been identified that may have a direct role in OP-induced delayed neurotoxicity. Given their ability to disrupt Ca 2+ homeostasis, a key aim of the current work was to investigate the effects of sub-lethal neurite outgrowth inhibitory levels of OPs on the Ca 2+ -dependent enzyme tissue transglutaminase (TG2). At 1–10 µM, the OPs phenyl saligenin phosphate (PSP) and chlorpyrifos oxon (CPO) had no effect cell viability but induced concentration-dependent decreases in neurite outgrowth in differentiating N2a neuroblastoma cells. The activity of TG2 increased in cell lysates of differentiating cells exposed for 24 h to PSP and chlorpyrifos oxon CPO (10 µM), as determined by biotin-cadaverine incorporation assays. Exposure to both OPs (3 and/or 10 µM) also enhanced in situ incorporation of the membrane permeable substrate biotin-X-cadaverine, as indicated by Western blot analysis of treated cell lysates probed with ExtrAvidin peroxidase and fluorescence microscopy of cell monolayers incubated with FITC-streptavidin. Both OPs (10 µM) stimulated the activity of human and mouse recombinant TG2 and covalent labelling of TG2 with dansylamine-labelled PSP was demonstrated by fluorescence imaging following SDS-PAGE. A number of TG2 substrates were tentatively identified by mass spectrometry, including cytoskeletal proteins, chaperones and proteins involved protein synthesis and gene regulation. We propose that the elevated TG2 activity observed is due to the formation of a novel covalent adduct between TG2 and OPs.

Effects of historic and projected climate change on the range and impacts of an emerging wildlife disease - Stephen J. Price; William T. M. Leung; Christopher J. Owen; Robert Puschendorf; Chris Sergeant; Andrew A. Cunningham; Francois Balloux; Trenton W. J. Garner; Richard A. Nichols (Global Change Biology, 2019)
The global trend of increasing environmental temperatures is often predicted to result in more severe disease epidemics. However, unambiguous evidence that temperature is a driver of epidemics is largely lacking, because it is demanding to demonstrate its role among the complex interactions between hosts, pathogens, and their shared environment. Here, we apply a three‐pronged approach to understand the effects of temperature on ranavirus epidemics in UK common frogs, combining in vitro, in vivo, and field studies. Each approach suggests that higher temperatures drive increasing severity of epidemics. In wild populations, ranavirosis incidents were more frequent and more severe at higher temperatures, and their frequency increased through a period of historic warming in the 1990s. Laboratory experiments using cell culture and whole animal models showed that higher temperature increased ranavirus propagation, disease incidence, and mortality rate. These results, combined with climate projections, predict severe ranavirosis outbreaks will occur over wider areas and an extended season, possibly affecting larval recruitment. Since ranaviruses affect a variety of ectothermic hosts (amphibians, reptiles, and fish), wider ecological damage could occur. Our three complementary lines of evidence present a clear case for direct environmental modulation of these epidemics and suggest management options to protect species from disease.

Controls on Arctic glacier-fed river water temperature - Christopher J. Mellor; Stephen J. Dugdale; Grace Garner; Alexander M. Milner; David M. Hannah (Hydrological Sciences Journal, 2017)

Late Pleistocene climate inferences from a water balance model of Jakes Valley, Nevada (USA) - Cornelia Barth; Douglas P. Boyle; Benjamin J. Hatchett; Scott D. Bassett; Christopher B. Garner; Kenneth D. Adams (Journal of Paleolimnology, 2016)